2021
DOI: 10.3389/fgene.2021.760744
|View full text |Cite
|
Sign up to set email alerts
|

Low APOA-1 Expression in Hepatocellular Carcinoma Patients Is Associated With DNA Methylation and Poor Overall Survival

Abstract: Background: Hepatocellular carcinoma (HCC) is the most frequent fatal malignancy, and it has a poor prognosis. Apolipoprotein 1 (APOA-1), the main protein component of high-density lipoproteins, is involved in numerous biological processes. Thus, this study was performed to detect the clinical significance of APOA-1 mRNA, APOA-1 expression, and APOA-1DNA methylation in patients with HCC.Methods: Data mining was performed using clinical and survival data from the Cancer Genome Atlas (TCGA) and Oncomine database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…By inhibiting the MAPK pathway, APOA1 alone delayed the cell cycle and decreased the growth of HCC cells [ 40 ]. Nevertheless, low levels of APOA1 in HCC patients were associated with poor prognoses [ 41 , 42 ]. Such adverse outcomes might be brought on by a tumor load that damages the liver severely or by hepatic function loss after radiotherapy, chemotherapy, or surgery.…”
Section: Discussionmentioning
confidence: 99%
“…By inhibiting the MAPK pathway, APOA1 alone delayed the cell cycle and decreased the growth of HCC cells [ 40 ]. Nevertheless, low levels of APOA1 in HCC patients were associated with poor prognoses [ 41 , 42 ]. Such adverse outcomes might be brought on by a tumor load that damages the liver severely or by hepatic function loss after radiotherapy, chemotherapy, or surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in renal clear cell carcinoma, poor OS and DFS are linked to increased APOA1 mRNA levels (25). Reportedly, APOA1 functions as a tumor suppressor, and its reduced methylation can be considered a promising prognostic marker in liver cancer (26). In colorectal cancer, decreased serum levels of APOA1 are linked to higher staging, systemic inflammation and poor patient prognosis (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…However, the level of methylation may fluctuate as a result of the genetic regulatory processes underlying diverse pathological disorders (29,30). According to previous studies, low expression of APOA1 in renal cell carcinoma may result from increased DNA methylation of the APOA1 gene (25) and Guo et al (26) revealed that patients with liver cancer with high levels of APOA1 DNA methylation had significantly longer progression-free survival time than those with low methylation. However, the correlation between DNA methylation and APOA1 expression level in BLBC has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative proteomic analysis showed that the expression of APOA1 protein was significantly down-regulated by 22% in HCC with hepatitis C virus (HCV) [ 44 ]. Guo et al reported that the expression level of APOA1 mRNA in the serum of HCC patients with liver cancer was significantly lower than that of healthy people, and high expression of APOA1 mRNA obviously correlated with better overall survival in the Chinese cohort [ 45 ]. These independent studies support the credibility of our results.…”
Section: Discussionmentioning
confidence: 99%